Robôs nas mídias sociais: uma análise sobre a gênese e o desenvolvimento do fenômeno social bots. - Barbosa, Bruno Rafael Gueiros (2018)
The use of robots in social media gains notoriety at the same time that political events reach a high potential of diffusion of the information through the internet, making it difficult to identify reliable sources and the differentiation between facts and lies, in a post-truth scenario. The dissertation aims to perform an interpretative analysis on the genesis and development of the phenomenon called social bots from a theoretical-conceptual revision of the post-industrial society and the information age. The paper contextualizes historically and describes the environment in which social bots emerge, technological advances, sociocultural transformations of the 21st century, interference in public debate, the influence of science fiction on the phenomenon and recent research on the subject. The conceptualizations and contextualizations start from a historical explanation and the analysis of processes, exposing necessary and sufficient conditions for the manifestation of social bots. In addition to the literature, a survey of seventy-eight scientific articles on automated accounts in digital social networks published on the Periódicos Capes website. The work points out possibilities of investigation of the phenomenon and evidences the interdisciplinary character of social bots, which are object of research in areas of knowledge such as Computer Science, Communication Sciences, Social Sciences, Political Science and Health Sciences.